Diverging Trends of Palm Cooking Oil Prices and Food Inflation in Makassar City, Indonesia - Farida Russa; Sri Mardiyati; Muh. Arifin Fattah; Mohammad Natsir; Nurdin (International Journal of Business and Quality Research, 2026)
This study analyzes the volatility and trends of non-packaged and packaged palm cooking oil prices in traditional and modern markets and their correlation with monthly food inflation in Makassar City, Indonesia, over the period January 2021–December 2025. Monthly secondary time‑series data on retail palm cooking oil prices were obtained from the Food Security Agency of South Sulawesi Province, while food inflation data were sourced from Statistics Indonesia. Trend analysis using linear least squares and Pearson correlation were employed. In traditional markets, non-packaged palm cooking oil prices were relatively more stable (coefficient of variation, CV=0.1347) than packaged cooking oil grade I (CV=0.1430) and grade II (CV=0.1478), whereas in modern markets, packaged cooking oil grade I was slightly more stable (CV=0.1723) than grade II (CV=0.1745). Price trends were significantly upward for all product types, with monthly increases of Rp75.93/liter (non-packaged), Rp71.87/liter (packaged I), and Rp56.99/liter (packaged II) in traditional markets, and Rp127.05/liter and Rp107.71/liter for packaged grades I and II in modern markets, respectively (p < 0.01). Monthly food inflation for the food subgroup exhibited high volatility (CV=4.0836) but a statistically non‑significant declining trend of 0.0081 percentage points per month. Non-packaged and packaged cooking oil prices were strongly and positively correlated (r=0.739, p<0.001), indicating integrated price movements across market channels, while their correlations with food inflation were weakly negative and statistically insignificant (non-packaged: r=−0.168, p=0.199; packaged: r=−0.129, p=0.324). These results imply that, despite pronounced and synchronized increases in palm cooking oil prices, short‑run monthly food inflation in Makassar was driven more by other food commodities and macroeconomic factors than by palm cooking oil alone.